Judah Magnes the prophetic politics of a religious binationalist - Barak-Gorodetsky, David (University of Nebraska Press, 2021)
"Judah Magnes, an intellectual biography of the Reform rabbi, American Zionist leader, and inaugural Hebrew University chancellor, analyzes how theology and politics intertwined to drive Magnes's writings and activism-especially his championing of a binational state against all odds"--